2018
DOI: 10.1186/s12955-018-0872-4
|View full text |Cite
|
Sign up to set email alerts
|

Chinese translation and psychometric testing of the cardiac self-efficacy scale in patients with coronary heart disease in mainland China

Abstract: BackgroundA person’s self-efficacy plays a critical role during the chronic management process of a health condition. Assessment of self-efficacy for patients with heart diseases is essential for healthcare professionals to provide tailored interventions to help patient to manage the disease.ObjectiveTo translate and test the psychometric properties of the Chinese version of Cardiac Self-efficacy Scale (C-CSES) as a disease-specific instrument for patients with coronary heart disease (CHD) in mainland China.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…The validity and reliability of the Cardiac Self-Efficacy scale has been established in research. [26][27][28][29]35 No studies were found that had used the scale with caregivers. In this study, the Cronbach alpha for SE-CS was 0.75 for patients and 0.74 for caregivers; SE-MF was 0.79 for patients and 0.76 for caregivers.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The validity and reliability of the Cardiac Self-Efficacy scale has been established in research. [26][27][28][29]35 No studies were found that had used the scale with caregivers. In this study, the Cronbach alpha for SE-CS was 0.75 for patients and 0.74 for caregivers; SE-MF was 0.79 for patients and 0.76 for caregivers.…”
Section: Self-efficacymentioning
confidence: 99%
“…14 Previous self-efficacy research has mostly involved a single assessment of either patients or caregivers. [5][6][7]14,[25][26][27][28][29][30] Such an individualised approach ignores the interdependency of behaviours or beliefs within the patient and partner relationship. 31 Because patients and family caregivers are affected by the patients' health status, interactions in patient and caregiver dyads are inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…A paper-and-pencil questionnaire as opposed to a digital one, along with printed advertisements posted in public areas would be bene cial to also include non-netizens within the study population. Moreover, further studies investigating optimism bias and self-e cacy though the General Self-E cacy Scale [26] may be helpful to explore how people cope with the threats of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…25 The scale is widely used in China, and the reliability and validity are good. 26 The scale consists of 10 items with each item scoring from 1 to 4, and the aggregate score ranges from 10 to 40. The standard score gets from the aggregate score divided by 10.…”
Section: Assessment Of Self-efficacymentioning
confidence: 99%